A case study of the language ideology within Armenian families in Kazakhstan - Turgaleyeva, Akmaral (Nazarbayev University Graduate School of Education, 2017)
This thesis is a case study which investigates the language ideology, language practices and ethnic identity construction among Armenians who were either deported during the Soviet regime or immigrated for other reasons to Kazakhstan. Armenians are a multilingual speech community in Kazakhstan where the process of the language shifts from the heritage language, Armenian, to the national and dominant languages, Kazakh and Russian are not completed yet. The thesis investigates the connection between two fields of research; language ideology and ethnic identity construction. The thesis presents a case study analysis of two Armenian families using a two level conceptual framework (macro, and micro). The observation, which was non-participatory, occurred in home contexts during a ten days period. During these observation sessions, semi-structured interviews regarding the maintenance of the mother tongue, attitudes and beliefs towards language use and the social, multiliteracy and ethnic practices were conducted. The findings indicate the connection between the macro and the micro level, where the macro is an official language policy, economic and social factors and individual families’ language perceptions, and the micro is language practices at a home. The complexity of Kazakhstani language situation and the rapid social, political and economic changes that are taking place in the community make this study particularly valuable in raising awareness of language challenges in immigrant families.
Keywords: language ideology; Armenian families; ethnic identity construction; language practices; multilingual speech community; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education